Performance Improvement Of OOFDM Systems Based On Advanced Logarithmic Companding Technique - Kareem, Ali N.; Abdul Satar, Sinan M.; A. Husein, Mohammed; Al-Hashime, Liqaa A.; Al-Suhail, Ghaida A. (Discoveries in Agriculture and Food Sciences, 2018)
High peak-to-average power ratio (PAPR) is a common problem in Orthogonal Frequency Division Multiplexing (OFDM) transmissions. In this paper, an advanced logarithmic companding technique is interested to reduce this factor due to their flexibility and low complexity. We evaluate the performance of the proposed advanced logarithmic technique comparing with typical logarithmic and un-companded schemes via simulations in Intensity Modulation/Direct Detection Optical Orthogonal Frequency Division Multiplexing (IM/DD OOFDM) system. The proposed advanced logarithmic Companding technique guarantees the improved performance in terms of Bit Error Rate (BER) and Quality Factor (QF) while reducing PAPR effectively and efficiently by modifying the amplitude of the transmitted signals. Our results confirm that the suggested scheme exhibits a good ability to reduce PAPR and a good BER performance based on the use the both of (k and y) factors to be chosen in relation to acceptable or desired PAPR, BER, and QF requirements. At the complementary cumulative distribution function (CCDF) of 10-3, the PAPR value of our proposed scheme is about 6.4 dB lower than those of un-companded signal at best control factor used of y=0.1, accordingly the QF is 11.8 dBm and the BER is 4.9×10-5.